Determinação da variabilidade espacial de características químicas do solo - Requia, Daner Seixas (2022)
Humanity faces great obstacles in guaranteeing a good agricultural management system based on the spatial and temporal variation of its properties. The present work aims to characterize the spatial variability of soil chemical properties (P, K, pH and base saturation) and to study the need for input application, as well as to compare the soil fertility conditions for the years 2012, 2017 and 2020, for the same management area. By studying the data collected for the three sampling years, it was possible to analyze the behavior of the soil chemical attributes in different plots of the experimental area of UFSM. The data were analyzed with Office Excel 2016 software, reconfigured into shapefile format and loaded into QGIS Desktop 3.20.1 software, allowing IDW interpolation and the use of geostatistics in the preparation and analysis of maps. Based on the results obtained, it was concluded that the application of variable rate significantly reduced the spatial and temporal variability of the areas and the creation of the maps allowed the identification of homogeneous zones.